Teacher's Creativity As A Mediator For The Influence Of The School Climate And Instructional Leadership - Khansa Rohadatul Aisy Rabbani, Eka Suhardi, Bibin Rubini (Universitas Pakuan, 2023)
This study aims to test the causality relationship model of school climate, instructional leadership and teacher creativity on learning effectiveness. The method used in this study is a quantitative method with a path analysis approach. Data collection was carried out by distributing questionnaires to 137 public elementary school civil servant teachers in Central Bogor District as the research sample. The results of the study show that 1) the causality relationship between school climate, instructional leadership, and teacher creativity is confirmed on learning effectiveness; 2) there is a positive direct effect of school climate on learning effectiveness with a path coefficient value (βy1 = 0.238); 2) there is a positive direct effect of instructional leadership on learning effectiveness with a path coefficient value (βy2 = 0.322); 3) there is a positive direct effect of teacher creativity on learning effectiveness with a path coefficient value (βy3 = 0.358); 4) there is a positive direct effect of school climate on teacher creativity with a path coefficient value (β31 = 0.395); 5) there is a positive direct effect of instructional leadership on teacher creativity with a path coefficient value (β32 = 0.395); 6) there is a positive indirect effect of school climate on the effectiveness of learning through teacher creativity with a path coefficient (β31βy3 = 0.141); 7) there is a positive indirect effect of instructional leadership on learning effectiveness with a path coefficient (β32βy3 = 0.192). This research has implications for the higher the school climate, instructional leadership and teacher creativity, the higher the effectiveness of learning.